Sistemas de manejo do solo para a produção de abobrinha de tronco (Curcubita pepo) - BIANCHINI, Cristiano (2013)
The use of different conservation techniques provides conditions to maintain the productive potential of soils, deserving attention of the researches in the area. Thus, the objective was to evaluate the production of zucchini trunk (Cucurbita pepo) comparing the conventional cropping systems and direct planting. This experiment was conducted in the Experimental Campus UTFPR - Two neighbors under a Red Nitosoil. The experimental design was randomized blocks with split plots. We evaluated two systems of cultivation, direct and conventional drilling. In the winter period were used cover crops of single oat in Conventional Planting - (CP) and Direct Planting (DP) and a consortium of oat, vetch and radish also implemented in DP. We performed two periods of fertilization located in pits: one before crop sowing of winter covers (Advance) and another shortly after management with roller-knife prior to sowing squash (Normal). The organic fertilization was resulted from composting poultry litter. The culture of zucchini was implanted in September. The harvest fruit was made when the same achieved commercial standard between 15 and 20 cm. After termination of the cycle of zucchini whole area was weeded and received a polyculture corn + leguminous, corn being deployed in the same pits that contained zucchini and legume cultivation between rows. The variables analyzed were the fruits: mass (kg), circumference (cm) length (cm), number of fruits and cycle. The assessment of soil refers to the stock of carbon (C) and nitrogen (N) of the soil and the organic matter fractionation. The cover crops were evaluated for the production of dry matter and the content of N in vegetable waste. The systems of management of soil and fertilization times interfered in the length and number of fruits produced. The tillage system was more productive at the end of the experiment. The concentrations of N and C of the soil and the COP were not influenced by tillage systems and times of fertilization. The early fertilization affected the levels of N in the soil after three cycles of cultivation, being smaller than the system of regular fertilization.